Utilización de la metodología six sigma para el mejoramiento del proceso de adquisiciones en los tiempos de entrega de las compras en una empresa dedicada a la producción de productos químicos (cloro) situada en la ciudad de Guayaquil - Franco, Omayra (2009)
This study establishes the effectiveness of the implementation of Six Sigma methodology in improving the delivery time of purchases of goods for a company dedicated to the production of chemicals (chlorine) in the city of Guayaquil. We describe the Six Sigma methodology at different stages of the DMAIC process and its application in the project. It also describes the improvements implemented, and a comparison between the results obtained before and after the action taken, is also a tool which consists of a control system, which has reports of control charts to determine whether the process is within certain parameters. Conclusions and recommendations.